EFEK LIKOPEN TERHADAP GAMBARAN MIKROSKOPIK LIMPA TIKUS BETINA SPRAGUE DAWLEY - Yuliani, Sapto (Pharmaciana, 2011)
Carotenoid compound, include licopene and lutein, has ability to increaseimmune system. One of organs included in immune system is spleen. The objective of thestudy is to observe the effect of licopene to the histopathologic appearance of ratspleen. Twenty female Sprague Dawley rat, 1 month old, 100 grams of weight devideinto 4 groups. The first group got licopene dosage 3 ug/kg of body weight, the secondgroup got licopene dosage 6 ug/kg of body weight, the third group got corn oil (vehiclecontrol) and the fourth group got aquadest. The treatment were given during 17 days,orally. At the day 14, the first, second and third groups were injected by aloxansubcutaneuslly. Three days after injection of aloxan, all of rats were sacrified, spleenwere taken in order to histopathological examination. Histopathologic appearances ofspleen were analized descriptivelly. The result showed that licopene dosage 6 ug/kg ofbody weigh able to increase centrum germinativum formation of spleen white pulp morethan licopene dosage 3 ug/kg of body weight. Base on the result can be concluded thatlicopene administration can increase centrum germinativum formation of spleen whitepulp.